Protective Effect of Vitamin E on Endosulfan Induced Testicular Toxicity in Swiss Mice (Mus musculus) - Kumar Bhatt, Girima Nagda*, Habiba Bano and Devendra (Journal of Experimental Sciences, 2011)
The present study was aimed to evaluate the role of vitamin E against the testicular toxicity induced by endosulfan. 8-10 weeks old, 24 healthy male animals were randomly selected and equally divided into 4 groups. Group I served as control group (C); group II endosulfan group (ES); group III vitamin E group (VE) and group IV vitamin E plus endosulfan group (VE+ES). Group C animals were given only vehicle the olive oil; in groups ES and VE+ES endosulfan was administered orally at a dose of 2.45 mg/kg b.w.; in groups VE and VE+ES, vitamin E was administered orally at a dose of 50 mg/kg b.w. In group VE+ES, vitamin E was administered 1 hour prior to endosulfan administration. All treatments were given continuously for 15 days. Endosulfan intoxication resulted in decreased testis weight tend severe histopathological changes which included shrunken and distorted seminiferous tubules and atrophy in the tissue. It was observed that administration of vitamin E minimized the endosulfan induced damage. Thus it can be concluded that pretreatment with vitamin E can alleviate the damage caused to testis by endosulfan.